Psychotherapeutic tools in dealing with negative psychoemotional states by example of online games - Пучина, Ольга (Psychosomatic Medicine and General Practice, 2023)
This text is the thesis of the poster presentation of the conference «Psychosomatic Medicine: science and practice» which took place on November 2-3, 2023 on the Mediamed portal. The following is devoted psychotherapeutic tools in dealing with negative psychoemotional states by example of online games.